Análise energética de bebida mista de extrato hidrossolúvel de soja e suco de amora - Uliana, Maíra Rodrigues [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (EIA Energy in Agriculture, 2010)
The objective of this study was to characterize the energy of the mixed drinks with soybean extract and blueberry juice, wich were developed at Drinks Lab, at Faculdade Ciências Agronômicas, UNESP, campus of Botucatu. The raw materials were soybeans (variety BRS 213), mulberry (genre Morus), citrus pectin and sugar. The mixed drink was made with different proportions of soymilk and mulberry juice (1:1, 1:1,5 and 1:2, respectively, m/m) and different concentrations of soluble solids (10, 12 and 14 °Brix). The soymilk, the mulberry juices and the mixed drinks were chemically analyzed, and from the chemistry analysis the energy values were quantified. The energy values of soybean extracts of this work ranged from 29,9 to 31,8 kcal 100 g-1, the mulberry juice from 29,9 to 33 kcal 100 g-1. Already, the energy values of the mixed drinks ranged from 41,60 to 60,50 kcal 100 g-1, which was conclude that solid soluble content of the mixed drink has a direct relation with the energy value of it.

O objetivo deste estudo foi caracterizar energeticamente bebidas mistas de extrato hidrossolúvel de soja (EHS) e suco de amora, que foram desenvolvidas no Laboratório de Bebidas, da Faculdade de Ciências Agronômicas, UNESP, Campus de Botucatu. As matérias-primas foram soja (variedade BRS 213), amora (gênero Morus), pectina cítrica e açúcar. A bebida mista foi fabricada em diferentes proporções de EHS e suco de amora (1:1; 1:1,5 e 1:2; respectivamente; m/m) e diferentes concentrações de sólidos solúveis (10, 12 e 14 °Brix). Os EHS, os sucos de amora e as bebidas mistas foram analisados quimicamente e a partir das análises químicas os valores energéticos foram quantificados. Os valores energéticos dos EHS deste trabalho variaram entre 29,9 a 31,8 kcal 100 g-1, os do suco de amora 29,9 a 33 kcal 100 g-1. Já, para as bebidas mistas, os valores energéticos variaram entre 41,60 a 60,50 kcal 100 g-1, permitindo concluir que os teores de sólidos solúveis das bebidas mistas produzidas guardam uma relação direta com os valores energéticos das mesmas.
Energy analysis of mixed drink of soybean extract and mulberry juice
Keywords: Non-alcoholic beverage; Soymilk; Energy; Bebida não alcoólica; Leite de soja; Valor energético